F recasting Stochastic Model of Maximum Temperature O 11te Mean for Benghazi City Using Seasonal Forecasting Methods - طاهره د. فارس; العقيلي أ. عبدالرحمن (Dirasat in Economics and Business, 2004)
The seasonal forecast have any methods to apply ,we want !11 find out which method is the :st and which of them can be plied for forecasting the high : rnperature mean for Benghazi city , we made a study for the decomposition,winter's and box Jenkins seasonal methods. we compared these three methods to conclude that the box -Jenkins method is the best along with determining tne forecasting stochastic model of high temperature mean of Benghazi city.